Risk Instability and the Pattern of Foreign Direct Investment in the Middle East and North Africa Region. (IMF Working Papers; Working Paper ;, 2004)
This paper demonstrates that instability associated with investment risk is critical in explaining the level of foreign direct investment for the Middle East and North Africa (MENA) countries, which generally have higher investment risk than developed countries. The empirical results support this hypothesis, whether either the standard deviation or the interquartile range is used as a measure of instability, in a dynamic panel model. The paper recommends a reorientation of policies toward those with a longer-term focus in order to help lower the degree of risk instability for MENA countries.